Sodium humate-functionalised superabsorbent hydrogels for heavy metals and organic dyes remediation in aqueous systems - Rapaiee, Hikmat Hidayat Muhammad; Julaihi, Dzureen; Nordin, Mohamad Izzat Arif; Liew, Fui Kiew; Sim, Siong Fong; Chiam, Chel Ken; Than, Leslie Thian Lung; Lin, Chin Yik; Tajuddin, Nazrizawati Ahmad; Lam, Su Shiung; Wang, Lin Chi; Tan, Cindy Soo Yun (Elsevier B.V., 2025)
Interpenetrating polymer network (IPN) hydrogels have emerged as robust and adaptable platform for wastewater and environmental remediations. Their interconnected architectures provide high mechanical stability, tunable surface chemistry and porosity, making them ideal for simultaneous removal of diverse contaminants in complex aqueous systems. Conventional hydrogels often suffer from low adsorption performance of dissolved pollutants due to structural fragility, limited crosslinking, leading to poor exposure of active sites. Herein, superabsorbent IPN hydrogels were fabricated using covalently-crosslinked poly (acrylic acid) grafted with sodium humate (PAA-HA), poly(acrylamide-co-1-vinylimidazole) (P(AAm-co-VIm)) and physically-crosslinked poly(vinyl alcohol) (PVA). Altering polymer composition allows facile control over surface area, thermal properties and water permeability of IPNs, all of which significantly affect their adsorption effectiveness. IPN1 (PVA/PAA-HA) proved to be more effective for Pb(II) separation with adsorption capacity of 93.12 mg g−1, whilst higher affinity for MB with adsorption capacity of 96.30 mg g−1 of IPN2 (PVA/PAA-HA/P(AAm-co-VIm)) indicates its potential for the dye removal. Simultaneous adsorption capacities of Pb(II), Cu(II) and MB by IPN1 in the ternary environment, with cumulative adsorption capacity of 107.03 mg g−1, surpassing the IPN1's adsorption capacities of single pollutant, further highlighting its high versatility in complex environment with multiple contaminants. The Pb(II) and Cu(II) adsorption mechanisms adopt the Langmuir isotherm via chemisorption. The IPNs are not only thermally stable with high adsorption capacities, but can be easily regenerated and reused. The superabsorbent IPNs are viable candidates for simultaneous removal of heavy metals and dyes, offering a significant step forward in sustainable wastewater treatment.